REFORMING THE ISLAMIC ECONOMIC AND ADMINISTRATION SYSTEM DURING THE UMAYYAD DYNASTY - Muhammad Ridho Nur (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2021)
The rule of the Bani Umayah was not strictly an Evil government as described by history. However, the Bani Umayan administration had advantages in various fields, especially in administration and an established economy. Friction with old empires such as Persia and Byzantium had influenced the Umayyad administration system. The filing of the Bani Umayah was more orderly, and the balance sheets began to be compiled in Arabic after the translation efforts of various documents started. This was done because the Bani Umayah area was extensive, starting from France, Italy, Sicily, Spain, North Africa to China and Russia's borders. The author conducted a literature study, collected verification documents, and reinterpreted them. The author rewrote the Umayah Bani economy's historical development, which had unique features, especially in the financial administration midwives. That was carried out by reformers such as Abdul Malik bin Marwan and Umar bin Abdul Aziz who had aged a country with experienced upheaval. Avoid premature destruction. They renewed the monetary system by creating their own currency, which had intrinsic value and did not depend on the Roman Empire and increased production to support the stability of a coin that not only relies on the strength of a more stable gold currency but was also supported by a factor of production which was also a factor. Prominent in a country that has a large area in realizing its economic stability.